2014
DOI: 10.1007/s13191-014-0380-0
|View full text |Cite
|
Sign up to set email alerts
|

“Split Cast Mounting: Review and New Technique”

Abstract: For the fabrication of a prosthesis, the Prosthodontist meticulously performs all the steps. The laboratory technician then make every effort/strives to perform the remaining lab procedures. However when the processed dentures are remounted on the articulator, some changes are seen. These changes may be divided into two categories: Pre-insertion and post-insertion changes, which deal with the physical properties of the materials involved (Parker, J Prosthet Dent 31:335-342, 1974). Split cast mounting is the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The indirect process of fabrication offers better access for creating natural occlusal and interproximal design. While the degree of conversion influences fracture resistance and wear resistance, the time for proper degree of conversion is not patient-dependent during indirect fabrication [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The indirect process of fabrication offers better access for creating natural occlusal and interproximal design. While the degree of conversion influences fracture resistance and wear resistance, the time for proper degree of conversion is not patient-dependent during indirect fabrication [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…8 Scattered descriptive reports list the use of different materials such as plaster, sticky wax, masking tape, elastic adhesive bandage, custommade mounting jig using alginate or putty index, tin foil and bite registration material, dowel pins with plastic or metal sleeves and screws, and washers to aid in remounting casts on dental articulators. [9][10][11][12][13] Nogueira et al 1 reported that the standard index-groove is the easiest and most popular technique. According to Scandrett and Hanson, 10 accurate remounting is fundamental for the fabrication of removable and fixed prostheses and, therefore, should be an integral part of the dental curriculum.…”
Section: Introductionmentioning
confidence: 99%
“…Although clinical removal is considered an important step in complete denture fabrication, an ideal split-cast technique has not been described. The paucity of literature comparing the performance and accuracy of previously reported split-cast techniques [9][10][11][12][13] for remounting warrants further investigation, particularly to update dental education on the technique providing the best outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations